The Effect of Macroeconomic Indicators and Governance as Demand Factors on Tax Ratio - Dita Sari Puspitarini; Arief Budi Wardana (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
This study aims to complement the many studies on the tax ratio (tax ratio) in supply factors. In addition to knowing the effect of supply factors on the tax ratio, this study was conducted to determine the impact of demand factors on the tax ratio managed by the DGT at the provincial level. The supply factors in this study include macroeconomic variables and economic structure (GRDP of the Agricultural Sector). Meanwhile, the demand factors in this study include the quality of governance implementation, income inequality, and fiscal decentralisation. The research method used is quantitative research by utilising panel data. The results show that the variables of economic growth, income inequality, and voice hurt the tax ratio. The economic structure variables (agricultural sector GDP) and unemployment rate affect the tax ratio positively. The fiscal decentralisation, accountability, and inflation rate variables do not affect the tax ratio.